Copper-chromium contact material surface alloy film for vacuum circuit breaker and preparation method of copper-chromium contact material surface alloy film

By plating CuCrNb alloy film on the CuCr alloy substrate and annealing treatment, the problem of coarse and uneven structure of CuCr contact material is solved, and its arc ablation resistance and service life are significantly improved.

CN119876876AActive Publication Date: 2025-04-25XI AN JIAOTONG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510085844.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing CuCr contact materials have poor ablation resistance due to their thick and uneven structure, which makes them difficult to meet the higher requirements of high-capacity and high-voltage power systems for contact reliability and service life.

Method used

The CuCrNb alloy film is coated on the surface of the CuCr alloy substrate and annealed to generate a uniform Cu phase and intermetallic compound phase Cr2Nb to improve the arc dispersion ability and voltage withstand strength of the contact surface.

Benefits of technology

The contact's arc ablation resistance is significantly improved, the service life of the contact is extended, and after 10 vacuum breakdowns, the average ablation depth is reduced to 1/2 of the CuCr substrate, and the area of ​​the arc ablation area increases to 3 times that of the CuCr substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876876A_ABST
    Figure CN119876876A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-chromium contact material surface alloy film for a vacuum circuit breaker and a preparation method of the copper-chromium contact material surface alloy film, and belongs to the technical field of contact material surface modification. The preparation method of the alloy film on the surface of the copper-chromium contact material for the vacuum circuit breaker comprises the following steps: by taking a Cu target, a Cr target and an Nb target as target materials, depositing a CuCrNb alloy film on a CuCr alloy substrate by adopting a magnetron sputtering method to obtain a CuCr alloy substrate on which the CuCrNb alloy film grows; and the CuCr alloy substrate on which the CuCrNb alloy film grows is subjected to annealing treatment under inert atmosphere protection, Cu phases on the surface of the CuCrNb alloy film are regulated and controlled to be evenly distributed in the annealing process, Cr2Nb phases are generated, and the copper-chromium contact material surface alloy film is obtained. According to the CuCrNb alloy thin film prepared by the method, the surface arc dispersion capability of the contact, the stability in the discharging process and the voltage resistance strength are improved, so that the arc ablation resistance of the contact is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of contact material surface modification, and more specifically to a copper-chromium contact material surface alloy film for a vacuum circuit breaker and a preparation method thereof. Background Art

[0002] As a key component for controlling the on and off of circuits, vacuum circuit breakers play an important role in power distribution networks, power generation facilities, substations, and many industrial fields. As the development trend of power systems moves towards larger capacity, higher voltage, and smaller size, the performance requirements for contact materials are also increasing. The core component of the vacuum circuit breaker is the contact, which controls the opening and closing of the circuit. During the breaking process, the contact will generate a vacuum arc, and the transient high temperature of the arc will cause severe ablation on the contact surface. The ablation damage mode and contact ablation morphology will affect its electrical performance and reliability. If the ablation is concentrated in a small area, it will accelerate the failure of the contact material. Therefore, in addition to having high electrical and thermal conductivity, the contact material should also have good arc dispersion ability, so that the arc can be quickly dispersed on the surface without concentrated ablation.

[0003] The CuCr alloy mainly used in vacuum circuit breakers has excellent electrical and thermal conductivity and good arc erosion resistance. However, with the development of large-capacity and high-voltage power systems, the vacuum circuit breaker industry has put forward higher performance requirements for CuCr contacts. To further improve the arc erosion resistance of CuCr contacts, it is necessary to more finely control the composition and organization of the contacts. However, due to the constraints of the overall CuCr alloy contact material preparation method, such as powder mixed sintering, vacuum casting, vacuum infiltration and arc melting, it is difficult to accurately control the composition, phase composition and microstructure distribution of the alloy. Only micron-scale organization can be obtained and the distribution is uneven. It is impossible to obtain good arc dispersion ability, and it is difficult to meet the higher requirements for contact reliability and service life. Summary of the invention

[0004] In view of the above problems, the present invention provides a copper-chromium contact material surface alloy film for vacuum circuit breakers and a preparation method thereof. The present invention plates a CuCrNb alloy film on the surface of a CuCr alloy substrate, and generates a uniform Cu phase and an intermetallic compound phase Cr2Nb phase after annealing. The CuCrNb alloy film improves the arc dispersion ability of the contact surface, the stability of the discharge process and the withstand voltage strength, thereby improving the arc ablation resistance of the contact, and solving the problem of poor ablation resistance of the existing CuCr contact material due to coarse and uneven structure.

[0005] The first object of the present invention is to provide a method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker, comprising the following steps:

[0006] A CuCrNb alloy film is deposited on a CuCr alloy substrate by magnetron sputtering using a Cu target, a Cr target and a Nb target as target materials, so as to obtain a CuCr alloy substrate on which the CuCrNb alloy film is grown.

[0007] The CuCr alloy substrate on which the CuCrNb alloy film is grown is annealed at 400°C to 850°C under inert atmosphere protection. During the annealing process, the Cu phase on the surface of the CuCrNb alloy film is uniformly distributed and a Cr2Nb phase is generated to obtain a copper-chromium contact material surface alloy film.

[0008] For example, the annealing temperature is 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0009] In a preferred embodiment of the present invention, the annealing time is 1 hour to 8 hours. For example, the annealing time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable.

[0010] In a preferred embodiment of the present invention, the annealing temperature is 850°C.

[0011] In a preferred embodiment of the present invention, the annealing treatment time is 1 hour.

[0012] In a preferred embodiment of the present invention, in the magnetron sputtering method, the sputtering current of the Cu target is 3.5A to 6.5A, for example, the sputtering current of the Cu target is 3.5A, 4A, 4.5A, 5A, 5.5A, 6A, 6.5A, etc.

[0013] The sputtering current of the Cr target is 1.3A to 7A. For example, the sputtering current of the Cr target is 1.3A, 1.5A, 2A, 2.5A, 3A, 3.5A, 4A, 4.5A, 5A, 5.5A, 6A, 6.5A, 7A, etc.

[0014] The sputtering current of the Nb target is 6A to 7A. For example, the sputtering current of the Nb target is 6A, 6.2A, 6.4A, 6.6A, 6.8A, 7A, etc., but is not limited to the listed values. Other values ​​not listed within the above numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, the sputtering deposition time is 100 min to 230 min, for example, the sputtering deposition time is 100 min, 130 min, 150 min, 170 min, 190 min, 210 min, 230 min, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the purity of the Cu target, the Cr target and the Nb target are all ≥99.9%.

[0017] In a preferred embodiment of the present invention, the sputtering gas pressure is 0.2Pa~0.3Pa, for example, the sputtering gas pressure is 0.2Pa, 0.22Pa, 0.24Pa, 0.26Pa, 0.28Pa, 0.3Pa, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0018] The second object of the present invention is to provide a copper-chromium contact material surface alloy film for vacuum circuit breaker prepared by the above preparation method.

[0019] In a preferred embodiment of the present invention, the atomic percentage of metal elements in the copper-chromium contact material surface alloy film is: Cu 50% to 55%, Nb 10% to 39%, and the rest is Cr, which is 100% in total.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adjusts the temperature and time of the annealing treatment to achieve the regulation of the solid solution and precipitation state of Cu and Cr phases, so that the surface Cu phase is evenly dispersed and distributed, and the vacuum arc dispersion performance of the film is improved. The present invention adopts a magnetron sputtering method to prepare a CuCrNb alloy film on the surface of a CuCr contact substrate. After annealing at 400°C to 850°C, fine and evenly distributed Cu particles can be precipitated in the supersaturated solid solution phase. The Cu particles are conducive to reducing the duration of the arc on the surface and are more dispersed, avoiding the appearance of concentrated ablation holes. Under the premise of ensuring good electrical conductivity of the contact material, the dispersion ability of the vacuum arc is greatly improved, and the generation of concentrated ablation is reduced, thereby improving the vacuum breakdown stability of the contact and extending the service life of the contact.

[0022] The Cu particles precipitated from the grains to the surface of the vacuum arc ablation-resistant copper-chromium-based film prepared by the present invention are all nanometer-scale. Because during the contact breaking process, when the arc is initially generated, a "cathode spot" will be formed first, and electrons will escape from the cathode spot to form a current path, and then the arc will be formed. The scale of the cathode spot is about micrometer level. For traditional micrometer-scale materials, the cathode spot is smaller than the grain and phase size. After the arc is formed, the arc will only burn the phase in its own area first, and concentrated ablation and pits will easily occur. The smaller nanometer scale is smaller than the size of the cathode spot. After the arc is generated, the Cu phase at the location is not enough to maintain its combustion. If the arc wants to continue to burn, it can only move. Therefore, the advantage of the nanometer-scale film over the traditional integral alloy is that it can better allow the arc to move and diffuse on the surface without concentrated ablation.

[0023] The present invention forms a CuCrNb alloy film by adding an appropriate amount of Nb to a CuCr binary alloy. After annealing, a Cr2Nb phase is formed between the Cr and Nb elements. The Cr2Nb phase has the advantages of a high melting point and a low work function, and can provide more arc-starting sites for the film. At the same time, the formation of a high melting point phase can further improve the withstand voltage strength of the film. The withstand voltage strength of the vacuum arc ablation-resistant CuCrNb alloy film prepared by the present invention is more than 1 times higher than that of the CuCr matrix. The average ablation depth after 10 vacuum breakdowns is less than 1 / 2 of that of the CuCr matrix, and the arc ablation area is 3 times that of the CuCr matrix, which significantly improves the arc dispersion performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the XRD diagram of the vacuum arc ablation resistant copper-chromium based film of Example 1.

[0025] Figure 2 This is a microscopic morphology of the vacuum arc ablation resistant copper-chromium based film of Example 1.

[0026] Figure 3 This is the EDS energy spectrum component distribution diagram of the vacuum arc ablation resistant copper-chromium based film of Example 1, wherein a is the Cu element, b is the Cr element, and c is the Nb element.

[0027] Figure 4 This is a diagram showing the change in cutoff value of the vacuum arc ablation resistant copper-chromium based film and the CuCr contact substrate of Example 1 during 10 vacuum breakdown processes.

[0028] Figure 5 This is a graph showing the change in voltage resistance of the vacuum arc ablation resistant copper-chromium based film and the CuCr contact substrate of Example 1 during 10 vacuum breakdown processes.

[0029] Figure 6It is a graph showing the change in cutoff value of the vacuum arc ablation resistant copper-chromium based film of Examples 1 to 4 during 10 vacuum breakdown processes.

[0030] Figure 7 It is a graph showing the change in voltage resistance of the vacuum arc ablation resistant copper-chromium based films of Examples 1 to 4 during 10 vacuum breakdown processes.

[0031] Figure 8 This is the result diagram of the vacuum arc ablation resistant copper-chromium-based film of Example 1 after 10 vacuum breakdowns, wherein a is the morphology diagram of the ablation area, and b is the 3D contour diagram of the corresponding area in a.

[0032] Fig. 9 This is the result of 10 vacuum breakdowns of the CuCr50 alloy contact substrate in the control group, where a is the morphology of the ablation area and b is the 3D contour of the corresponding area in a.

[0033] Fig.10 It is the morphology image of the ablation area and the 3D contour image of the corresponding area of ​​the vacuum arc ablation resistant copper-chromium-based film of Examples 2 to 4 after 10 vacuum breakdowns, wherein a is the morphology image of the ablation area in Example 2, b is the 3D contour image of the corresponding area in Figure a, c is the morphology image of the ablation area in Example 3, d is the 3D contour image of the corresponding area in Figure c, e is the morphology image of the ablation area in Example 4, and f is the 3D contour image of the corresponding area in Figure e.

[0034] Fig.11 This is a microscopic morphology of the vacuum arc ablation resistant copper-chromium based film of comparative example 1.

[0035] Fig.12 This is the EDS energy spectrum component distribution diagram of the vacuum arc ablation resistant copper-chromium based film of Example 1, wherein a is the Cu element, b is the Cr element, and c is the Nb element.

[0036] Fig.13 This is a result diagram of the vacuum arc ablation-resistant copper-chromium-based film and the CuCr contact substrate of Example 1 after 10 vacuum breakdowns, wherein a is a morphology diagram of the ablation area, and b is a 3D contour diagram of the corresponding area in a.

[0037] Fig.14 This is a microscopic morphology of the vacuum arc ablation resistant copper-chromium based film of comparative example 2.

[0038] Fig.15 This is the EDS energy spectrum component distribution diagram of the vacuum arc ablation resistant copper-chromium based film of Example 2, wherein a is the Cu element and b is the Cr element.

[0039] Fig.16This is a result diagram of the vacuum arc ablation-resistant copper-chromium-based film and the CuCr contact substrate of Example 2 after 10 vacuum breakdowns, wherein a is a morphology diagram of the ablation area, and b is a 3D contour diagram of the corresponding area in a. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention adopts magnetron sputtering technology to adjust the process parameters to achieve the regulation of CuCr film grains, phase composition, and organizational structure. The CuCr film deposited by magnetron sputtering can form a supersaturated solid solution phase, and then the precipitation of each phase in the film and the solid solution phase ratio can be controlled by combining annealing treatment, thereby changing the performance of the film. Adding high melting point alloy elements to the CuCr alloy film can improve the high temperature resistance of the film. If the alloy elements have a lower work function, it is easier to emit electrons and improve the dispersion of arc energy on the surface. Adding Nb elements to the CuCr alloy can inhibit the precipitation and growth of the Cu phase, so that a small amount of precipitated Cu particles are evenly dispersed on the contact surface. Annealing in a specific temperature range will form a high melting point intermetallic compound Cr2Nb, which can further improve the voltage resistance of the contact material, thereby enhancing the arc ablation resistance of the film.

[0042] The diffusion of elements depends on the temperature and time of annealing. Metal atoms diffuse quickly at high temperatures, and are easy to diffuse and precipitate to form large particles. Time controls the amount of metal precipitation and the speed of growth. Therefore, in the annealing process, the present invention reduces the time under high temperature annealing to control the amount of metal precipitation and the degree of growth; when the annealing temperature is reduced, the diffusion can be slowed down and the precipitation amount can be reduced. At this time, increasing the annealing time can precipitate as much as possible, and it is easier to control the degree of precipitation.

[0043] Example 1

[0044] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0045] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0046] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0047] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 6.5 A, 7.0 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 100 min to obtain a CuCrNb alloy film with a thickness of 3.5 μm;

[0048] The atomic percentages of the three metals in the prepared film are: Cu 53%, Cr 36%, and Nb 11%.

[0049] 4) The CuCrNb alloy film was annealed at 850° C. in a quartz tube protected by argon gas, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film, which was recorded as CuCrNb-Th-850.

[0050] Example 2

[0051] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0052] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0053] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0054] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 4.7 A, 3.5 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 130 min to obtain a CuCrNb alloy film with a thickness of 2.9 μm;

[0055] The atomic percentages of the three metals in the prepared film are: Cu 52%, Cr 26%, and Nb 22%.

[0056] 4) The film was annealed at 650° C. in a quartz tube protected by argon gas, kept at this temperature for 8 hours, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film.

[0057] Example 3

[0058] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0059] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0060] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0061] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 4.0 A, 2.0 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 200 min to obtain a CuCrNb alloy film with a thickness of 2.5 μm;

[0062] The atomic percentages of the three metals in the prepared film are: Cu 51%, Cr 18%, and Nb 31%.

[0063] 4) The film was annealed at 700° C. in a quartz tube protected by argon gas, kept at this temperature for 4 hours, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film.

[0064] Example 4

[0065] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0066] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0067] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0068] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 3.5 A, 1.3 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 230 min to obtain a CuCrNb alloy film with a thickness of 2.7 μm;

[0069] The atomic percentages of the three metals in the prepared film are: Cu 50%, Cr 11%, and Nb 39%.

[0070] 4) The film was annealed at 700° C. in a quartz tube protected by argon gas, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film.

[0071] Example 5

[0072] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0073] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0074] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0075] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.3 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 3.5 A, 1.3 A and 6 A, respectively, and a -60 V bias voltage was applied to the substrate. The deposition time was 230 min to obtain a CuCrNb alloy film;

[0076] 4) The film was annealed at 400° C. in a quartz tube protected by argon gas, kept at this temperature for 6 hours, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film.

[0077] Example 6

[0078] The present embodiment provides a method for preparing a vacuum arc ablation resistant copper-chromium based film, comprising the following steps:

[0079] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0080] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0081] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.25 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 5 A, 3 A and 6.5 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 230 min to obtain a CuCrNb alloy film;

[0082] 4) The film was annealed at 500° C. in a quartz tube protected by argon gas, kept at this temperature for 5 hours, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film.

[0083] Comparative Example 1

[0084] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0085] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0086] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and Cu, Cr and Nb targets were sputtered at target currents of 6.5 A, 7.0 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 100 min to obtain a CuCrNb alloy film with a thickness of 3.5 μm;

[0087] The atomic percentages of the three metals in the prepared film are: Cu 53%, Cr 36%, and Nb 11%.

[0088] 4) The CuCrNb alloy film was annealed at 900° C. in a quartz tube protected by argon gas, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film, which was recorded as CuCrNb-Th-900.

[0089] Comparative Example 2

[0090] 1) Using CuCr50 alloy as a substrate, the substrate is ground, polished, cleaned, and dried, and then fixed on a workpiece rack in a vacuum chamber of a coating equipment, and each metal target is installed on a target position of the vacuum coating equipment;

[0091] 2) Evacuate the vacuum chamber of the magnetron sputtering equipment to a pressure of ≤5×10 -3 Pa, argon gas was introduced into the vacuum chamber to make the gas pressure 0.2 Pa, and a -500 V bias was applied to the substrate, and the substrate surface was cleaned by glow sputtering for 30 minutes.

[0092] 3) Argon gas was introduced into the vacuum chamber of the magnetron sputtering equipment to make the gas pressure 0.2 Pa, and the Cu target and Cr target were sputtered at target currents of 5.7 A and 7.0 A, respectively, and a -60 V bias was applied to the substrate. The deposition time was 70 min to obtain a CuCr alloy film with a thickness of 2.5 μm;

[0093] The atomic percentages of the three metals in the prepared film are: Cu 51%, Cr 49%.

[0094] 4) The CuCr alloy film was annealed at 850° C. in a quartz tube protected by argon gas, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace to obtain a vacuum arc ablation resistant copper-chromium based film, which was recorded as CuCr-Th-850.

[0095] Figure 1 This is the XRD of the CuCrNb-Th-850 alloy film after annealing in Example 1. It can be seen that the CuCrNb-Th-850 alloy film after annealing is mainly composed of Cu and Cr phases. At the same time, due to the presence of Nb element, Cr2Nb phase appears after annealing.

[0096] Figure 2 The microscopic morphology of the CuCrNb-Th-850 alloy film prepared in Example 1 shows that after the annealing treatment, fine and dispersed Cu particles are precipitated on the surface of the CuCrNb alloy film. The surface composition distribution of the CuCrNb-Th-850 alloy film obtained by EDS spectrum testing is as follows: Figure 3 As shown, the elements in the CuCrNb-Th-850 alloy film are evenly distributed, and there is no area with obvious element segregation.

[0097] The electrical breakdown experiment was carried out according to the following steps:

[0098] 1) Fix the sample prepared in the embodiment on the breakdown sample stage in the vacuum electrical breakdown equipment, and adjust the distance between the tungsten needle and the sample stage to a suitable position;

[0099] 2) Evacuate the vacuum chamber of the vacuum electrical breakdown equipment to a pressure of ≤6×10 -4 After Pa, adjust the voltage to 10 kV and shorten the distance between the sample stage and the tungsten needle until breakdown occurs;

[0100] 3) After repeating the above operation 10 times, take out the sample and observe the surface morphology and regional contour of the ablation position.

[0101] The CuCr50 alloy was ground, polished, cleaned and dried before electrical breakdown experiments as a control group, recorded as the CK group.

[0102] The CuCr50 alloy coated with the CuCrNb-Th-850 alloy film in Example 1 was subjected to 10 vacuum electrical breakdown tests. The change of the cutoff value in the vacuum electrical breakdown is shown in FIG. Figure 4 The cutoff value of the CuCrNb alloy film is stable at 1-2A, while the cutoff value of the CuCr substrate in 10 breakdowns gradually increases from 6A to 8A. Therefore, compared with the CuCr material without CuCrNb-Th-850 alloy film in the CK group, the CuCrNb-Th-850 alloy film can significantly reduce the breakdown cutoff value and enhance the stability of the arc discharge process.

[0103] Figure 5 The voltage withstand strength changes of CuCr alloy and CuCrNb-Th-850 alloy film in CK group during 10 vacuum electrical breakdowns. The voltage withstand strength of CuCrNb-Th-850 alloy film can reach up to 12×10 7 V·m -1 , and stabilized at 10×10 7 V·m -1 , while the highest withstand voltage strength of the CuCr-free alloy in the CK group is 6.5×10 7 V·m -1 , and gradually decreased to 4.8×10 7 V·m -1 It can be seen that the CuCrNb-Th-850 alloy film has higher voltage resistance.

[0104] Figure 8 and Fig. 9 The morphology of the ablation area of ​​the CuCr50 alloy contact containing the CuCrNb-Th-850 alloy film prepared in Example 1 and the CuCr50 alloy contact in the CK group after 10 vacuum electrical breakdowns and the 3D contour map of the corresponding area are shown respectively. After 10 breakdowns, the breakdown depth of the CuCrNb-Th-850 alloy film is about 36μm, which is significantly shallower than that of the CuCr alloy in the CK group, and the ablation area of ​​the CuCrNb-Th-850 alloy film is larger, about 3 times that of the CuCr substrate, indicating that the CuCrNb-Th-850 alloy film is conducive to the dispersion of the arc on the surface of the contact substrate.

[0105] The vacuum arc ablation resistant copper-chromium based films in Examples 1 to 4 were subjected to 10 vacuum electrical breakdown tests. The changes in the cutoff value during vacuum breakdown are shown in FIG. Figure 6 The cutoff values ​​in 10 breakdowns were all below 3A, and the cutoff values ​​of the CuCrNb films of Examples 1 and 2 were the most stable, indicating that the discharge process of the CuCrNb films in these examples was stable during breakdown. As the amount of Nb added increased, the cutoff value gradually increased.

[0106] Figure 7 The voltage resistance changes of the vacuum arc ablation resistant copper-chromium-based films in Examples 1 to 4 during 10 vacuum electrical breakdowns. The voltage resistance was maintained above 7A during the 10 breakdowns and did not decrease significantly with the increase in the number of breakdowns, indicating that the vacuum arc ablation resistant copper-chromium-based films did not fail under multiple breakdowns. The voltage resistance of the CuCrNb-Th-850 alloy film in Example 1 was stable at 11×10 7 V·m -1 , has the best withstand voltage performance, and the withstand voltage strength decreases slightly with the addition of Nb. This is because the Cu particles precipitated on the surface are uniform and fine. On the one hand, after the arc appears, the arc can be quickly diffused on the surface of the contact base. This diffusion process will quickly disperse and consume the energy of the arc, and evenly disperse the energy to multiple locations on the surface, so that concentrated ablation will not occur at a certain point. This can be seen from Figure 8 The surface ablation area is expanded and the ablation depth is shallow. On the other hand, the arc burning time can be prolonged. This can be seen from Figure 6 It can be seen from the cutoff value curve that the cutoff value is lower, which indicates that the arc discharge is stable during the extinction process.

[0107] Fig.10 The morphology of the ablation area of ​​the vacuum arc ablation-resistant copper-chromium-based film in Examples 2 to 4 after 10 vacuum electric breakdowns and the 3D contour map of the corresponding area. During the breakdown process, the arc was diffused on the surface, and no concentrated ablation occurred. By comparing the range of the ablation area, the ablation area of ​​the CuCrNb-Th-850 alloy film in Example 1 is the largest, and the average ablation depth is about 36μm, which has the best arc diffusion performance in Examples 1 to 4.

[0108] Fig.11 The microscopic morphology of the CuCrNb-Th-900 alloy film prepared in Comparative Example 1 shows that after the CuCrNb alloy film is annealed at this temperature, large Cu particles are precipitated on the surface, and the Cu particles have grown significantly, and their distribution and size are no longer controllable. The surface composition distribution of the CuCrNb-Th-900 alloy film obtained by EDS spectrum testing is shown in Figure 1. Fig.12 As shown, the distribution of Cu element in the CuCrNb-Th-900 alloy film shows obvious segregation, and Cu is distributed over a large area on the surface, which is consistent with the morphology.

[0109] Fig.13The 3D contour diagram of the ablation area morphology and the corresponding area of ​​the CuCrNb-Th-900 alloy film CuCr50 alloy contact prepared in Comparative Example 1 after 10 vacuum electric breakdowns. After 10 breakdowns, the breakdown depth of the CuCrNb-Th-900 alloy film is about 49μm, which is significantly deeper than the CuCrNb-Th-850 alloy film in Example 1. At the same time, a clearly visible concentrated ablation area has appeared, indicating that the uniform and dense distribution of Cu particles on the surface of the CuCrNb-Th-850 alloy film is conducive to the dispersion of the arc on the surface of the contact base, while the unregulated growth and uneven distribution of Cu particles will lead to the concentration of arc ablation, and cannot achieve a good arc dispersion effect.

[0110] Fig.14 The microscopic morphology of the CuCr-Th-850 alloy film prepared in Comparative Example 2 shows that after the CuCr alloy film without Nb element is annealed at this operating temperature, large Cu particles have precipitated and grown on the surface, and the distribution is extremely uneven. The distribution and size of Cu particles are uncontrollable at this temperature. Therefore, the CuCr alloy film without Nb element cannot withstand the welding treatment required by the contact. The surface composition distribution of the CuCr-Th-850 alloy film obtained by EDS spectrum test is shown in Figure 2. Fig.15 As shown, the distribution of Cu element in the CuCr-Th-850 alloy film shows obvious segregation, and Cu is distributed over a large area on the surface, which is consistent with the morphology.

[0111] Fig.16 The 3D contour diagram of the ablation area morphology and the corresponding area of ​​the CuCr-Th-850 alloy film CuCr50 alloy contact prepared in Comparative Example 1 after 10 vacuum electric breakdowns. After 10 breakdowns, the breakdown depth of the CuCr-Th-850 alloy film is about 55μm, which is significantly deeper than the CuCrNb-Th-850 alloy film in Example 1. At the same time, a clearly visible concentrated ablation area has appeared, indicating that the CuCrNb-Th-850 alloy film with the addition of Nb element can better control the uniform and dense distribution of surface Cu particles at high temperature, which is conducive to the dispersion of the arc on the contact base surface. The growth and uneven distribution of Cu particles in the CuCr film without Nb will lead to the concentration of arc ablation, and cannot achieve a good arc dispersion effect.

[0112] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0113] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker, characterized in that: The following steps are involved: Using Cu target, Cr target and Nb target as target materials, a CuCrNb alloy film is deposited on a CuCr alloy substrate by magnetron sputtering to obtain a CuCr alloy substrate with a CuCrNb alloy film grown thereon; The CuCr alloy substrate on which the CuCrNb alloy film is grown is annealed at 400°C to 850°C under inert atmosphere protection. During the annealing process, the Cu phase on the surface of the CuCrNb alloy film is uniformly distributed and a Cr2Nb phase is generated to obtain a copper-chromium contact material surface alloy film.

2. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: The annealing time is 1h to 8h.

3. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: The annealing temperature is 850°C.

4. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 3, characterized in that: The annealing time is 1 h.

5. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: In the magnetron sputtering method, the sputtering current of the Cu target is 3.5A to 6.5A, the sputtering current of the Cr target is 1.3A to 7A, and the sputtering current of the Nb target is 6A to 7A.

6. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: The sputtering deposition time is 100 min to 230 min.

7. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: The purity of the Cu target, Cr target and Nb target are all ≥99.9%.

8. The method for preparing a copper-chromium contact material surface alloy film for a vacuum circuit breaker according to claim 1, characterized in that: The sputtering gas pressure is 0.2Pa~0.3Pa.

9. A copper-chromium contact material surface alloy film for vacuum circuit breaker prepared by the preparation method according to any one of claims 1 to 8.

10. The copper-chromium contact material surface alloy film for vacuum circuit breaker according to claim 9, characterized in that: The atomic percentage of metal elements in the copper-chromium contact material surface alloy film is: Cu 50%~55%, Nb 10%~35%, and the rest is Cr, totaling 100%.

Citation Information

Patent Citations

  • Cr2Nb phase containing CuCr contact material preparing method

    CN110512114A

  • Vacuum arc-extinguishing chamber contact material surface coating and processing method thereof

    CN111074209A

  • Contact head for vacuum circuit breaker as well as preparation method thereof, vacuum circuit breaker and alloy coating material for vacuum circuit breaker contact head

    CN112126898A

  • High-pressure ablation resistant Wf-CuCrW contact and preparation method thereof

    CN117672727A

  • Preparation method of CuCrNb material for high voltage grade

    CN117816952A